ANALISIS TINGKAT KESADARAN HUKUM MASYARAKAT TENTANG PERNIKAHAN DI BAWAH UMUR DI KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Nova Angraini; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This research was motivated by a case that occurred in Kelayang District, Indragiri Hulu Regency. There have been446 pairs recorded from October 16, 2019 to May 2021. Where the age limit for marriage has been regulated in Law Number16 of 2019 concerning amendments to Law Number 1 of 1974 which regulates marriage. The formulation of the problem in this study is how is the level of legal awareness of the community about underage marriage in Kelayang District, Indragiri Hulu Regency. The purpose of this study was to find out how the level of legal awareness of the community about underage marriage in Kelayang District, Indragiri Hulu Regency. The research method in Kelayang District, Indragiri Hulu Regency is quantitative descriptive, the data collection instruments used in this study are questionnaires, observations, documentation and interviews consisting of 15 statements. The population in this study is the entire community of Kelayang District, amounting to 25,246 people. Sampling in this study using purposive sampling and with a sample of 100 people. Based on the results of the study, it can be concluded that overall data regarding the analysis of the level of public legal awareness about underage marriage in Kelayang District, Indragiri Hulu Regency is in the